DISARM is a widespread bacterial defence system with broad anti-phage activities. (January 2018) - Ofir, Gal; Melamed, Sarah; Sberro, Hila; Mukamel, Zohar; Silverman, Shahar; Yaakov, Gilad; Doron, Shany; Sorek, Rotem
Abstract The evolutionary pressure imposed by phage predation on bacteria and archaea has resulted in the development of effective anti-phage defence mechanisms, including restriction–modification and CRISPR–Cas systems. Here, we report on a new defence system, DISARM (defence island system associated with restriction–modification), which is widespread in bacteria and archaea. DISARM is composed of five genes, including a DNA methylase and four other genes annotated as a helicase domain, a phospholipase D (PLD) domain, a DUF1998 domain and a gene of unknown function. Engineering theBacillus paralicheniformis 9945a DISARM system intoBacillus subtilis has rendered the engineered bacteria protected against phages from all three major families of tailed double-stranded DNA phages. Using a series of gene deletions, we show that four of the five genes are essential for DISARM-mediated defence, with the fifth (PLD) being redundant for defence against some of the phages. We further show that DISARM restricts incoming phage DNA and that theB. paralicheniformis DISARM methylase modifies host CCWGG motifs as a marker of self DNA akin to restriction–modification systems. Our results suggest that DISARM is a new type of multi-gene restriction–modification module, expanding the arsenal of defence systems known to be at the disposal of prokaryotes against their viruses. A widespread anti-phage defence system, DISARM (defence island system associated with restriction–modification), is identified.